2013
DOI: 10.1002/eco.1360
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying transpirable soil water and its relations to tree water use dynamics in a water‐limited pine forest

Abstract: Knowledge of the relationship between soil water dynamics and tree water use is critical to understanding forest response to environmental change in water‐limited ecosystems. However, the dynamics in soil water availability for tree transpiration (Tt) cannot be easily deduced from conventional measurements of soil water content (SWC), notably because Tt is influenced by soil water potential (Ψs) that, in turn, depends on soil characteristics. Using tree sap flow and water potential and deriving depth‐dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 68 publications
6
86
0
Order By: Relevance
“…This supports the idea that the surface layer is the most important layer regarding water availability in the Caatinga biome for several reasons: it receives ephemeral pulses of rainfall; it contains the highest root length density; and it shows the most favorable hydraulic properties for water Caatinga forest, where the upper layer supplied up to 90% of the total water requirement . Other authors have also found transpiration to be controlled by soil water content of the surface layer KLEIN et al, 2014b;LIU et al, 2011;.…”
Section: Sampling Sitesmentioning
confidence: 89%
See 4 more Smart Citations
“…This supports the idea that the surface layer is the most important layer regarding water availability in the Caatinga biome for several reasons: it receives ephemeral pulses of rainfall; it contains the highest root length density; and it shows the most favorable hydraulic properties for water Caatinga forest, where the upper layer supplied up to 90% of the total water requirement . Other authors have also found transpiration to be controlled by soil water content of the surface layer KLEIN et al, 2014b;LIU et al, 2011;.…”
Section: Sampling Sitesmentioning
confidence: 89%
“…The concept of pulse water availability of short duration for arid regions has been reported, e.g., by Lauenroth et al (2014), Reynolds et al (2000), Sala and Lauenroth (1982) and Williams et al (2009). Klein et al (2014b) found that variability of hydraulic properties with soil depth plays an important role in water availability for plants, particularly in water-limited ecosystems. Table 4.5 and Figure 4.2 suggest that for the Caatinga biome the surface layer allows root water uptake to occur at lower (more negative) water potentials than in deeper layers.…”
Section: Sampling Sitesmentioning
confidence: 99%
See 3 more Smart Citations